Digital Participatory Governance and Public Trust in Special Autonomy Regions: A Public Value Framework for Inclusive Public Service Delivery in Aceh, Indonesia - Fathia Zuhaira (SWATANTRA, 2025)
Digital transformation has become a central agenda in contemporary public administration, particularly in decentralized and special autonomy regions where the legitimacy of government is closely linked to responsiveness, transparency, and the capacity to deliver inclusive public services. Aceh, Indonesia, offers a significant case for examining how digital participatory governance can contribute to public trust and public value creation within a special autonomy setting. This article develops a conceptual and policy-oriented framework for understanding the relationship between digital participation, collaborative governance, public trust, and inclusive service delivery in Aceh. Using a qualitative desk-based research design, the study synthesizes international literature on public value governance, collaborative governance, co-production, digital government, and trust in public institutions, supported by policy documents related to Indonesia’s Electronic-Based Government System and Aceh’s special autonomy context. The article argues that digital governance should not be reduced to the technical modernization of administrative procedures. Instead, it should be understood as a political-administrative process through which citizens, local communities, civil society, and public institutions co-produce public value. The findings identify four interrelated dimensions of digital participatory governance in special autonomy regions: institutional responsiveness, transparent information ecosystems, inclusive citizen engagement, and adaptive service integration. These dimensions form the basis of the proposed DPTI Framework: Digital Participation, Public Trust, Transparency, and Inclusion. The article concludes that digital transformation in Aceh will generate stronger public value only when supported by institutional legitimacy, participatory policy design, digital inclusion, and accountable local governance. The study contributes to government science and public administration by linking digital governance with special autonomy, trust-building, and public value creation in a post-conflict decentralized region.